Penguatan Peran Mahasiswa dalam Menciptakan Lingkungan Kampus yang Bersih dan Peduli Lingkungan : Penelitian - Hariani, Mila; Fitria, Elica Zuliatul (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The strengthening of student roles in creating a clean and environmentally conscious campus has proven effective in fostering a culture of environmental awareness. Students act as active change agents through participatory activities such as communal cleaning of campus areas and waterways, planting and maintaining edible and ornamental plants, and responsible waste management. This program applies the Asset-Based Community Development (ABCD) approach, emphasizing the utilization of local assets and collaboration among students, lecturers, and campus staff, thereby promoting collective awareness in maintaining cleanliness, sustainability, and campus aesthetics. Beyond the physical impact of a cleaner and healthier campus, the program enhances students’ knowledge, skills, and attitudes regarding environmental management. Educational activities, hands-on practices, and awareness campaigns cultivate values of mutual cooperation, responsibility, and social solidarity. The synergy between students, campus authorities, and the local community strengthens the sustainability of the program and serves as a replicable model of community engagement. Consequently, empowering students not only improves the campus environment but also prepares a generation that is environmentally conscious, responsible, and ready to face future sustainability challenges.